Pelatihan Kepenyiaran dan Sosialisasi melalui Program Acara “Ngobrol Pintar (Ngopi)” di Radio Basuma FM - Suprapto, Irawan; Daud, Rosy Febriani (TAAWUN, 2022)
The broadcasting field is growing rapidly according to the level of human civilization which is increasingly advancing with advances in communication technology. Radio is one of the electronic media for distributing information and forming communication and public opinion which has a very strategic role. In its development, radio has become a communicative, educative and entertaining medium, which only requires the sense of hearing so that it can be heard anywhere. As an electronic mass media, a lot of information about the social condition of North Lampung district and entertainment is packaged into a "Smart Chat" (Ngopi) program presented by students of the communications science study program at Muhammadiyah University of Kotabumi (UMKO) and in collaboration with Radio Bahana Surya Melati (BASUMA)) FM. Based on the background of the problem, problems can be formulated on how to provide information on the radio properly or radio broadcasts properly and how to socialize the Communication Studies Program to residents around North Lampung Regency. This service activity aims to provide training and broadcasting skills and socialization of the Communication Science study program to Communication Science students at the University of Muhammadiyah Kotabumi (UMKO). The method used in this service activity is by several methods, namely lectures, discussions, and questions and answers. Based on the results of the radio broadcasting training activities and the socialization of the communication science study program (Ilkom) through the "Smart Chat (Ngopi)" program, the theory related to the skills of using equipment (operating skills) of broadcasting training participants on BASUMA FM radio can be said that broadcasting training participants on BASUMA FM radio, almost master and can operate all broadcast equipment, however, in addition to mastering broadcast equipment, a broadcaster must also be able to turn on and turn off radio transmitters.